Screening for Nonalcoholic Fatty Liver Disease in Inflammatory Bowel Diseases: A Cohort Study Using Transient Elastography. Issue 1 (7th June 2018) - Saroli Palumbo, Chiara; Restellini, Sophie; Chao, Che-Yung; Aruljothy, Achuthan; Lemieux, Carolyne; Wild, Gary; Afif, Waqqas; Lakatos, Peter L; Bitton, Alain; Cocciolillo, Sila; Ghali, Peter; Bessissow, Talat; et al.
Abstract: Background: Inflammatory bowel disease (IBD) patients may be at risk for nonalcoholic fatty liver disease (NAFLD) due to chronic inflammation, hepatotoxic drugs, and alteration of the gut microbiota. Prospective data using accurate diagnostic methods are lacking. Methods: We prospectively investigated prevalence and predictors of NAFLD and liver fibrosis by transient elastography (TE) with associated controlled attenuation parameter (CAP) in IBD patients as part of a routine screening program. NAFLD was defined as CAP ≥248 dB/m. Significant liver fibrosis (stage 2 or higher out of 4) was defined as TE measurement ≥7.0 kPa. Predictors of NAFLD and significant liver fibrosis were determined by logistic regression analysis. Results: A total of 384 patients (mean age 42.4 years, 45.0% male, 64.6% with Crohn's disease) with no significant alcohol intake were included. Prevalence of NAFLD and significant liver fibrosis was 32.8% and 12.2%, respectively. Independent predictors of NAFLD were older age (adjusted odds ratio [aOR], 1.45; 95% confidence interval [CI], 1.15–1.82), higher body mass index (BMI; aOR, 1.31; 95% CI, 1.20–1.42) and higher triglycerides (aOR, 1.45; 95% CI, 1.01–2.09). Significant liver fibrosis was independently predicted by older age (aOR, 1.38; 95% CI, 1.12–1.64) and higher BMI (aOR, 1.14; 95% CI, 1.07–1.23). Extrahepatic diseases were more common in IBD patients with NAFLD compared with those without, namely chronic kidney disease (10.3 vs 2.3%; P < 0.001) and cardiovascular diseases (11.3 vs 4.7%; P = 0.02). Conclusions: NAFLD diagnosed by TE with CAP is a frequent comorbidity in IBD patients and is associated with extrahepatic diseases. Noninvasive screening strategies could help early diagnosis and initiation of interventions, including weight loss, correction of dyslipidemia, and linkage to care.